Moments of clarity : a study of higher education teachers' professional learning experiences and the transformational process of change in self-efficacy development : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Education at Massey University, Manawatū, New Zealand - Percy, Bridget Marie (Massey University, 2017)
This qualitative longitudinal study sought to understand ‘aha’ moments experienced by a group of early career higher education teachers in Aotearoa New Zealand and the role those moments played in the transformational process of change in teacher self-efficacy development. Self-efficacy theory was foregrounded throughout the study, transformation theory provided an established framework to understand the process of transformation, and the notion of threshold concepts was used to conceptualise the ‘aha’ moment and name potential teaching threshold concepts. Aotearoa New Zealand specific teacher self-efficacy studies are important because studies in other contexts have shown self-efficacy is a predictor of teacher motivation, resilience and persistence in the face of difficulties and self-efficacy is linked to successful student achievement. In understanding the relationship between ‘aha’ moments and how these contribute to teacher self-efficacy development, there is the potential for professional learning opportunities that support self-efficacy promotion. Eleven early career teachers shared their experiences of ‘aha’ moments and their interpretation of the role these played in their teacher self-efficacy development. This research found that ‘aha’ moments were personal learning realisations that contributed to change in teacher self-efficacy and that the transformational development of teacher self-efficacy can be understood as a process containing four distinct phases. Furthermore, the transformative ‘aha’ moments, and in particular those that constituted a teaching specific potential threshold concept, provided teachers with an enhanced awareness of teaching capability. Finally, mastery experiences (successful and unsuccessful) were the most commonly described source of efficacy information related to the teachers’ ‘aha’ moments.
Keywords: College teachers; In-service training; Self-efficacy; New Zealand